Palladium-silver chronology of IAB iron meteorites - Theis, K.; Schoenbaechler, M.; Benedix, Gretchen; Rehkämper, M.; Andreasen, R.; Davies, C. (Elsevier Science BV, 2013)
The extinct 107Pd–107Ag decay system (half-life 6.5 Ma)is a useful chronometer to constrain thethermal evolution of the IAB parent body.To this end, Pd/Ag concentrations and the Ag isotopecompositions of metals separated from 6 different IAB iron meteorites were determined. The samplesshow epsilon 107Ag variations between +0.1 and +15.8 with 108Pd/109Ag ratios between 38 and 200.The datacan be divided into two groups based on their petrology, each defining an isochron:a graphite andtroilite rich inclusion bearing group (A),with the IAB meteorites Toluca, Odessa and Canyon Diablo anda more silicate rich group (B), which includes Campo Del Cielo, Caddo County and Goose Lake. Usingthe initial abundance of 107Pd derived from carbonaceous chondrites, the corresponding age for thegroup (A) is18.7(±3.6/5.0) Ma after the start of the solar system and 14.9 (±2.5/4.9) Ma forthe group (B). This suggests that the last thermal event to reach high enough temperatures to meltmetal on the IAB parent body occurred within the first 15 Ma of our solar system.